1994
DOI: 10.1111/j.2044-8325.1994.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate education and the career orientation of professional engineers: Comparison between individuals from enhanced engineering courses and those from conventional engineering courses

Abstract: Previous research has distinguished between professional engineers who have a managerial career oriencation and those who have a technical orientation. One of the aims of' the Dainton enhanced engineering courses was to produce engineers who are managerially, rather than technically, oriented. As part of a large-scale evaluation of these courses, the career orientations of 744 students and 220 graduates from these programmes were com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Data collected in another part of this investigation indicated that students embarking on enhanced courses were already more favourably disposed towards business and commercial aspects of engineering at the outset of their studies than their conventional counterparts (Keenan 1993).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Data collected in another part of this investigation indicated that students embarking on enhanced courses were already more favourably disposed towards business and commercial aspects of engineering at the outset of their studies than their conventional counterparts (Keenan 1993).…”
Section: Discussionmentioning
confidence: 82%
“…Thus, studies of the career orientation of engineers (Barclay 1986;Keenan 1993;Allen and Katz 1988) show that many engineers wish to have careers as technical specialists rather than engineering managers. The Dainton enhanced courses are not designed for this career role, and the more exclusively technical focus of traditional courses may be more suited to this type of individual.…”
Section: Discussionmentioning
confidence: 99%
“…(''Interface '' 1996a, p. 39) Education is an important factor in the narrowing of engineering outlooks. A study which compared students in and graduates from conventional engineering courses in Britain with those in ''enhanced'' management-oriented engineering courses found that, while students who were more interested in management tended to choose or be selected for the ''enhanced'' engineering courses, these students had a declining technical orientation as they progressed through the courses compared with the students doing conventional engineering courses, indicating that engineering education is influential in forming graduate attitudes and career orientations (Keenan 1994).…”
Section: Problems With Overly Scientific Approachmentioning
confidence: 99%
“…Career development has become a significant component of policy development in many countries, because of its potential impact on the labour market (RICHARD, 2005). The careers of engineers have been the subject of a series of studies that have in common the implicit assumption that the manufacturing of a country is dependent, at least in part, on the quality of its professional engineers (KEENAN, 1994). However, very promising engineers are being promoted to managerial positions as a way of recognizing their contribution to an organizations goals.…”
Section: Introductionmentioning
confidence: 99%
“…This fact, in addition to engineers orientations and expectations to be treated as professionals, has caused considerable tension and strain in the engineer-management relationship. This calls for changes in engineering management styles to maintain motivation and productivity (BLIGLIARDI;PETRONI;DORMIO, 2005;KEENAN, 1994).…”
Section: Introductionmentioning
confidence: 99%